Blending Martial Arts and Yoga for Health: From the Last Samurai to the First Odaka Yoga Warrior - Di Placido, Matteo (Frontiers in Sociology, 2020)
This paper introduces the case study of Odaka Yoga, an innovative style of postural yoga blended with martial arts elements which emphasizes the importance of practitioners’ health and processes of self-transformation as pivotal to the school’s ethos. More specifically, the paper explores how Odaka Yoga’s philosophical backdrops and practical repertoire, composed by a mixture of “exotic” resources such as Bushido, zen, yoga, and a constant reference to the ocean waves and biomechanics, constitute a very specific vision of health at the intersection of Western science and esoteric knowledge. Theoretically, the paper borrows from Jennings’ theory of martial creation and enriches it with some of the central analytical tools proposed by theorists such as Bourdieu and Foucault. Methodologically, it relies on a multimodal approach including discursive analysis of the school’s promotional materials, interviews with the founders and other key teachers, and observant participation of practitioners’ apprenticeship processes. More Specifically, this paper discusses the birth of Odaka Yoga as occurring at the intersection of Asian martial arts and yoga, as well as the founders’ biographical trajectories from the world of competitive martial arts and fitness, to yoga; it then turns to an examination of Odaka Yoga’s conception of health as a mixture of the Western biomedical model and the subtle body model of Asian traditions such as yoga and martial arts. It argues that the conception of health promoted by this school gives rise to the Odaka Yoga Warrior, the ideal-typical practitioner whose body is simultaneously exposed to the medical gaze and its imperatives of control, knowledge and manipulation; while it also deifies it, as it is animated by the elusive flows of energy (qi or prana) that prolonged practice aims to master. The paper concludes with a reflection on hybrid conceptions of health and the ubiquitous role of health discourses and narratives across sociocultural domains.